Factors influencing impact force profile and measurement accuracy in drop weight impact tests - Li, H.; Chen, Wensu; Hao, Hong (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Drop weight tests on RC beams have been intensively reported in literature. Load cells are commonly used to measure the impact force acting on the beam. Different researchers adopted different configurations, e.g., location of load cells in the test, which could affect the impact load measurement. Although various impact force profiles have been reported by different researchers, there is no systematic study regarding the influences of the test setup on the measured impact forces. Therefore, this study numerically investigates the influences of test setups on impact force measurement accuracy and impact force profile of RC beam under drop weight impact. It is found that when the load cell is embedded into drop weight, the mass distribution of drop weight causes the measured impact force to deviate from the actual contact force acting on the beam. To obtain the true impact force recorded by the load cell mounted at the rear of drop weight head, the drop weight mass ratio αd (i.e., mass of the drop-weight to mass of the head) should be lower than 20. Placing load cell between drop weight and beam changes the local contact stiffness of impact zone and thus leads to different impact force profiles. In addition, the drop weight to beam mass ratio within the range of 0.5 and 4.0 affects the relative velocity between drop weight and beam after the first impulse and hence results in different impact force profiles.